A landscape of me: images of a creativity worshop in ceará, Brazil - Morgado, Elsa Maria Gabriel (2018)
This article describes the production of paintings by college students during a Creativity Workshop. The workshop, a member of the PhD research in Educational Sciences, aimed at developing creative potential, through exercises, artistic expression and group experiences. In this qualitative research-action study, 30 students from the Vale do Acaraú State University (UVA), Sobral, Ceará, Brazil, participated. In the activity we use gouache paint, applied with the hands on wood paper. The results were paintings with free themes that presented in a playful and poetic way, snapshots of the students. The most explored themes were landscapes: the sea, the house, the tree, the flowers and sketches of the human figure. The vivid colors in the representation of nature dialogue with symbolic elements such as the home. In addition to the discussion about the artistic quality of the productions, it was important to experience the process, in which the paintings provided a reencounter with affective memories and with the creative potential of the students.